The Effectiveness of a Structured Sports Activity Program in Reducing Psychological Stress and Its Role in Mitigating Burnout Among Dormitory Students at Anbar University - Marwan Abdullateef AbdulJabbar (Indonesian Journal Publisher, 2026)
This study aimed to identify the effectiveness of a program based on structured sports activity in reducing psychological stress and its role in mitigating burnout among dormitory students at the University of Anbar, as well as analyzing the role that psychological stress plays in explaining the relationship between structured sports activity and burnout. The study was based on the hypothesis that the effect of sports activity is not limited to reducing burnout directly, but rather extends to an indirect effect through reducing psychological stress, as it is one of the main factors causing burnout. The researcher adopted the experimental approach using a pretest-posttest equivalent groups design (experimental and control). The study sample consisted of 25 students who were distributed into two groups: an experimental group that underwent the structured sports activity program, and a control group that did not undergo any intervention. The application of the program lasted for 7 weeks with two sessions per week, and included structured sports activities of an interactive nature aimed at (reducing psychological stress, improving emotion regulation, enhancing psychological balance). The study utilized a psychological stress scale and a burnout scale. The results showed statistically significant differences between the pre- and post-measurements in favor of the experimental group in the reduction of the level of psychological stress and burnout, and these results emphasize the importance of employing structured sports programs within psychological support strategies in the university environment, especially among dormitory students, due to their effective role in reducing psychological stress as a primary source of burnout, thereby limiting its manifestations and enhancing general mental health